Functional outcome in distal third tibial fractures treated with interlocking nailing - Thanigaimani, K. (International Journal of Research in Orthopaedics, 2016)
Background: The purpose of this study was to evaluate the functional outcome in distal third tibial fractures not extending into the ankle joint treated with interlocking nailing. Methods: Twenty eight patients of distal tibial fractures were admitted in our orthopaedic department .5 patients were lost to follow up. Hence 23 patients were studied. After initial resuscitation and immobilization, they were taken up for internal fixation. Depending upon their general condition and associated injuries the time interval for surgery varied from one day to two weeks. They were periodically followed at 6 weeks, 3rd month, 4th month, 6th month and every eight weeks thereafter, till fracture union. Results: No patient in the study went in for non-union. All the fractures united well. However two patients had osteomyelitis which was settled after nail removal and appropriate antibiotics. One had ankle stiffness. The outcome was analysed with Johner and Wruh criteria. Conclusions: The outcome of treatment of distal tibial fractures is mostly affected by the severity of the injury and associated complications or injury. The study showed that interlocking nailing gives good results in distal third tibial fractures.